Heritability of Health Behaviours - Suontama, Matilda (My University, 2024)
Health behavior significantly impacts life expectancy, the number of healthy life years, and overall life satisfaction. Health behaviours include any actions taken to promote, protect, or maintain health. Public health education has effectively increased awareness of the fundamentals of healthy behaviour among the general population. However, the practical implementation of these behaviours remains insufficient. A key underlying factor is that, similar to other traits, health behaviours are also heritable. This literature review summarizes the evidence on the heritability of four major health behaviours: dietary patterns, smoking behaviour, alcohol consumption, and physical activity. The primary focus is on prospective parent-child studies and twin studies. Twin studies are particularly valuable as they allow researchers to distinguish between traits influenced by shared environmental factors and those attributable to genetic heritability. Additionally, this review includes findings from twin, family, and genetic association studies. The key findings of these studies are compiled and presented as summaries and in tables. The review points to significant heritability of health behaviours persisting into middle age. Approximately half of the variance in these behaviours can be attributed to genetic factors. Of the four reviewed health behaviours, smoking behaviour and alcohol consumption exhibit higher heritability compared to dietary patterns and physical activity. Unexpectedly, the influence of shared environment, such as parental upbringing during childhood, showed minimal impact on behaviours in adulthood. The findings suggest that the influence of health education received during childhood might diminish into adulthood. On the other hand, the substantial genetic contribution to health behaviours in adults fosters empathy towards individuals affected by prevalent public health diseases largely influenced by one’s behaviour. However, while genetics significantly affect health behaviours, an individual’s environment also plays a crucial role. This offers hope: While inherited attributes are permanent, environment, such as residence and social networks, can be actively affected with possible positive health behaviour consequences.
Keywords: health behaviours, heritability, prospective parent-child association studies, twin studies